Youth as Agents of Strengthening Religious and Cultural Literacy through Local Wisdom in Pantan Cuaca, Gayo Lues - Ismail Khalidin (LaKaspia, 2026)
This study aims to analyze the role of young people as agents of strengthening religious and cultural literacy based on local wisdom in Pantan Cuaca District, Gayo Lues Regency. The research employed a qualitative approach with a descriptive research design through observation, interviews, and documentation. The informants consisted of youth, religious leaders, traditional leaders, village officials, and community members from Pantan Kota, Tetingi, and Remukut villages. The findings reveal that young people play an active role in strengthening religious literacy through the organization of Islamic study circles (pengajian) and majelis ta’lim, the provision of religious books and waqf copies of the Qur’an, and participation in grave-digging traditions as an expression of religious and social values. In strengthening cultural literacy, young people actively engage in communal work (gotong royong) and preserve traditional Gayo arts such as Saman Dance, Didong, and Debus. These activities have generated positive impacts on the community, including strengthening social solidarity and unity, enhancing religious and cultural knowledge, and reducing the potential for conflict, thereby fostering a more harmonious social life. The study concludes that young people hold a strategic position as agents of change who contribute to preserving religious and cultural values rooted in local wisdom amid the challenges of modernization and globalization